Eksplorasi Etnomatematika terhadap Alat Musik Demung pada Kesenian Krumpyung Kulon Progo (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
Culture in Indonesia covers all aspects of human life, one of which is education. Indonesia has a diverse culture, of course the goals and education system in Indonesia can be based on culture. One of the learning related to culture is ethnomathematics. Exploration of ethno mathematical learning can be done with Demung Musical Instruments in Krumpyung Arts. The research objectives are (1) to know the history, function, and form of the Demung Musical Instrument in Krumpyung Art (2) to find out the relationship between the Demung Musical Instrument in Krumpyung Art based on 6 fundamental activities according to Bishop. This study uses a descriptive method with a qualitative and ethnographic approach. Data collection techniques used are observation, interviews, and literature study. The results of this study describe aspects of fundamental activities according to the bishop, among others, counting the number of bamboo in Demung which consists of 6 bamboo slats at the top, 13 bamboo supports. The bamboo selection process takes 2-3 years. The mapping aspect is the selection of places and bamboo slats to produce the desired resonant tone. The measurement aspect is the length of the bamboo blades used to make musical instruments. The main aspects are the bamboo cutting strategy, bamboo selection, and how to play Demung. The historical explanation aspect is the art of krumpyung, especially the Demung musical instrument. Aspects of designing are visuals, patterns, and the location of the demong forms in creating the desired tone
Keywords: etnomatematika; demung; kesenian krumpyung